Innate Immune Response to Viral Infections at the Maternal-Fetal Interface in Human Pregnancy - Espino, Ana; El Costa, Hicham; Tabiasco, Julie; Al-Daccak, Reem; Jabrane-Ferrat, Nabila (Frontiers in Medicine, 2021)
The placenta, the first and largest organ to develop after conception, not only nurtures and promotes the development of the conceptus, but, it also functions as a barrier against invading pathogens. Early phases of pregnancy are associated with expansion of specific subsets of Natural Killer cells (dNK) and macrophages (dM) at the maternal uterine mucosa, the basal decidua. In concert with cells of fetal origin, dNK cells and dM orchestrate all steps of placenta and fetus development, and provide the first line of defense to limit vertical transmission. However, some pathogens that infect the mother can overcome this protective barrier and jeopardize the fetus health. In this review, we will discuss how members of the classical TORCH family (Toxoplasma, Other, Rubella, Cytomegalovirus and Herpes simplex virus) and some emerging viruses (Hepatitis E virus, Zika virus and SARS-CoV2) can afford access to the placental fortress. We will also discuss how changes in the intrauterine environment as a consequence of maternal immune cell activation contribute to placental diseases and devastating pregnancy outcomes.